2017
DOI: 10.1186/s13058-017-0883-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of somatic PI3K pathway and ERBB family mutations on pathological complete response (pCR) in HER2-positive breast cancer patients who received neoadjuvant HER2-targeted therapies

Abstract: BackgroundThe Cancer Genome Atlas analysis revealed that somatic EGFR, receptor tyrosine-protein kinase erbB-2 (ERBB2), Erb-B2 receptor tyrosine kinase 3 (ERBB3) and Erb-B2 receptor tyrosine kinase 4 (ERBB4) gene mutations (ERBB family mutations) occur alone or co-occur with somatic mutations in the gene encoding the phosphatidylinositol 3-kinase (PI3K) catalytic subunit (PIK3CA) in 19% of human epidermal growth factor receptor 2 (HER2)-positive breast cancers. Because ERBB family mutations can activate the PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…As shown in Table , 20 studies including 4392 patients were included in our meta‐analysis . Overall, PIK3CA mutation incidence in our meta‐analysis was 22.4% (range 7.7–39.0%).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As shown in Table , 20 studies including 4392 patients were included in our meta‐analysis . Overall, PIK3CA mutation incidence in our meta‐analysis was 22.4% (range 7.7–39.0%).…”
Section: Resultsmentioning
confidence: 98%
“…pCR was 28% for PIK3CA MT and 38% for PIK3CA WT. Seven studies were conducted in the United States, nine in Europe, and four in Asia . Two studies included objective response rate, while the others reported pCR as the endpoint in WT versus MT PIK3CA tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Interestingly, further results from the EMILIA trial showed that PFS was not affected by the PIK3CA mutational status in patients treated with TDM-1, while patients harbouring PIK3CA mutations, treated with standard HER2 therapy, had shorter PFS compared to PIK3CA wild-type patients (4.3 vs 6.4 months respectively). 41 More recently, Toomey et al 42 were the first to report that PI3KCA/ERBB mutations in patients receiving neoadjuvant docetaxel, carboplatin, trastuzumab and lapatinib may be more likely to experience pCR in comparison to patients with the wild-type gene. Of the overall patients 15% were HR-ERBB2−; 9% were HR-ERBB2+; 64% were HR+ ERBB2−; and 12% were HR+ ERBB2+.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of pro-proliferative signaling pathways such as PI3K/Akt/mTOR, Src, or MAPK is also associated with a worse prognosis and resistance in HER2+ breast cancer patients. Combinatorial treatment with agents that target these pathways, such as everolimus, AZD0530, or dasatinib improve survival in lapatinib-and trastuzumab-refractory patients [68][69][70] . The development of marker or gene assays, to better predict treatment response tailored to specific genetic and genomic features of the breast cancer would be helpful to prevent anti-HER2 treatment resistance.…”
Section: Mechanisms Of Lapatinib Resistancementioning
confidence: 99%